Microbiome and metabolomic changes in rabbits induced by Folium sennae - Houkang Ding; Ming Li; Ning Ma; Shahid Ali Rajput; Mikhlid H. Almutairi; Bader O. Almutairi; Zhaoqing Han; Aituan Ma; Dengshan Shiau (PLoS ONE, 2025)
Diarrhea is a serious health concern in livestock, affecting productivity and animal welfare. However, it remains a significant threat. Various practical therapies are being explored, such as prebiotics, probiotics, and organic acids, as well as chemical treatments including antibiotics, to combat this disorder. This study aims to explore the microbiome and metabolomic changes in rabbits with diarrhea. In the present study, diarrhea was induced in rabbits via oral gavage of Folium Sennae (FSAE), to assess body weights, diarrhea index, serum biochemical indicators, histopathology, microbiota, and metabolomics changes. Our study provides new insights into the mechanism of FSAE-induced diarrhea in rabbits and offers a novel mechanism for the interaction between gut microbiota, metabolomics, and gastrointestinal (GIT) dysfunction. Our results revealed that rabbits receiving FSAE showed a markedly higher diarrhea index and reduced body weight. Notably, levels of somatostatin, substance P, cholecystokinin, 5-hydroxytryptamine, vasoactive intestinal peptide, and acetylcholinesterase were significantly increased compared to control (P <  0.01). However, the levels of gastrin, motilin, enkephalin, and β-Endorphins were significantly decreased (P <  0.01). Microbial analysis revealed a significant reduction in microbial diversity (Shannon, Simpson, ACE, and chao1) and a decrease in Firmicutes, Campilobacterota, and Proteobacteria populations in FSAE-exposed rabbits. Additionally, 13 key metabolites associated with taurine and hypotaurine metabolism, alanine, aspartate and glutamate metabolism, starch and sucrose metabolism, histidine metabolism, and citrate cycle were identified in the colonic tissues. The present study concludes that FSAE-induced diarrhea in rabbits is associated with significant histopathological alterations in the colon, dysregulation of serum biochemical markers, and dysbiosis in metabolomics and gut microbiota. Our findings offer a novel model for investigating GIT dysfunction and its potential treatments.